2013
DOI: 10.1155/2013/378206
|View full text |Cite
|
Sign up to set email alerts
|

Chronologic versus Biologic Aging of the Human Choroid

Abstract: Several aspects of chronologic and biologic aging in the human choroid are reviewed from the literature. They often reveal methodological problems for age-dependent changes of the following parameters: choroidal thickness, choroidal pigmentation, choroidal vasculature and blood flow, and choroidal innervation. On reinterpreting some data of studies concerning Bruch's membrane, changes observed at different age points seem more likely to be nonlinear. Concluding from the data presented so far, chronologic aging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…This was also justified among the age group comparisons in which older age groups had thicker pericentral RPE layers (Table 5). May [26] reported that Bruch's membrane thickening started in the periphery and macular thickening was observed after 45 years of age. This may also explain why the central 1 mm RPE thickening was not identified in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This was also justified among the age group comparisons in which older age groups had thicker pericentral RPE layers (Table 5). May [26] reported that Bruch's membrane thickening started in the periphery and macular thickening was observed after 45 years of age. This may also explain why the central 1 mm RPE thickening was not identified in our study.…”
Section: Discussionmentioning
confidence: 99%
“…18 The BM is an acellular extracellular meshwork found between the RPE and the choroid and is known to undergo increased thickening during aging. 19 May 20 reported that thickening of the BM starts in the periphery and macular thickening was first observed from 45 years of age. Other authors proposed its linear correlation with age.…”
Section: Discussionmentioning
confidence: 99%
“…Such dual innervation balances the increase and decrease in choroid blood flow. Despite aging, the choroidal innervation patterns and neural transmitters remain unaltered to some extent [ 111 ]; however, some studies have suggested a decrease in adrenergic fibers and VIP(+) nerve fibers [ 122 , 123 , 124 ]. SP (+) and CGRP (+) ICNs have been identified in choroidal whole mounts, suggesting choroidal innervation by sensory nerves.…”
Section: Autonomic Control Of the Eyementioning
confidence: 99%